STRATEGI PERBANKAN SYARIAH DALAM MANAJEMEN ASET DAN LIABILITAS - Rani Raranta (Tamwil, 2020)
The purpose of this article is for readers to know what Islamic banking strategies are in managing their assets and liabilities. This research is classified as Library Research, while the nature of this research is descriptive qualitative, namely research that seeks to find solutions to existing problems based on data, by presenting, analyzing, and interpreting data. Data analysis techniques that take general things, then conclude to specific things. The results of this study can be concluded that if Islamic banks are able to maximize their benefits from well-managed and structured funding and financing and are able to produce optimal management of the risks faced by Islamic banks, then these Islamic banks can be said to be successful in their asset and liability management strategies. The ALMA strategy used by Islamic banks is Planning, Fund Management and Financing. The ALMA Strategy Quality Management can also minimize risks such as: Financing Risk, Liquidity Risk, Pricing Risk, Foreign Exchange Risk, Contingency Risk, Liquidity Risk, Gap Risk.